Agitacja bolszewicka i ruch komunistyczny na Wołyniu w okresie formowania polskiej administracji (1919-1921) - Hładyszuk, Serhij (Komunizm: System - Ludzie - Dokumentacja, 2015)
The article analyzes the bolshevik agitation and the beginnings of the communist movement in Volhyn during the formation of the Polish administration in 1919–1921. In various towns of Volhyn poor probolshevik people organized troops “Nation Bolsheviks” who have carried out robberies among the richer peoples. The author shows the almost weekly Volhyn occupation by the Red Army in summer 1920 and the process of forming the new government and communist proups. Most members of the revolutionary committees on occupied territories were Jews and Ukrainians. Short-term occupation of the Volhyn region by the Red Army ended with the start of the Polish counteroffensive from September 1920. In this time Polish administrarion again took to Volhyn. Part of the local Bolsheviks gone to the Eastern Ukraine, and some of them in future start to take part in the Communist Party of Western Ukraine.